Patterns of Kidney Diseases in Native Biopsies: A Single-Center Experience - Regina Anjani Budi Pratiwi; Shintia Christina; Dina Nilasari (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Kidney biopsy is the definitive diagnostic method for kidney disease, providing essential histopathological information for prognosis and treatment. However, in Indonesia, comprehensive data on kidney biopsy patterns remain limited, making it difficult to assess disease prevalence and epidemiological trends. Objective: To analyze the epidemiology of biopsy-confirmed kidney diseases in a single-center cohort and evaluate the distribution of clinical and histopathological diagnoses. Methods: A retrospective descriptive analysis was performed on patients who underwent a kidney biopsy at Siloam Hospital Kebon Jeruk between January 2021 and August 2024. Data on demographics, clinical manifestations, biopsy indications, histopathological findings, and immunofluorescence results were analyzed using descriptive statistics. Results: A total of 45 kidney biopsies were conducted, resulting in a biopsy rate of 5.24 per 1,000 individuals, higher among young adults (15–44 years). The median patient age was 43 years, with a nearly equal male-to-female ratio. Nephrotic syndrome was the leading clinical presentation (35.9%), followed by nephritic syndrome (33.3%). Hematuria and proteinuria (35.6%) were the most frequent biopsy indications. Glomerular diseases represented as majority of histopathological diagnoses, with focal segmental glomerulosclerosis (FSGS) being the most common finding (37.8%), followed by lupus nephritis and IgA nephropathy. A rare case of monoclonal gammopathy of renal significance was also identified. Conclusion: This study provided insight into biopsy-confirmed kidney disease patterns in Indonesia. The predominance of glomerular diseases, particularly FSGS, aligns with global trends. The low biopsy rate underscores the need for expanded nephrology services and further multicenter studies to develop a comprehensive national kidney disease registry.